Hubungan Motivasi Berprestasi dengan Hasil Belajar Mahasiswa Jalur Umum Program Studi D3 Kebidanan STIKes Dharma Husada Bandung - Endang Astiriyani (LPPM STIKES Guna Bangsa, 2015)
Objective : To find out the correlation between achievement motivation and student’s study achievement at D3 midwifery Spesific Program of STIKes Dharma Husada Bandung. Method : This study used analytical descriptive method with cross sectional approach. Data were gathered by using questionnaires given to the 2nd semester students. While the student’s study achievement were gained through documentation study of their KHS, Study Achievement Card. Result : The study shows the high motivation level 93 (71%), midle 38 (29%), low and very low are 0 (0%). Study achievement excellent with reward 20 (15,3%), very satisfaction 85 (64,9%), satisfaction 25 (19,1%), and need improvement 1 (0,8%).